1984
DOI: 10.1002/cjce.5450620119
|View full text |Cite
|
Sign up to set email alerts
|

The production of the antibiotic patulin in a three phase fluidized bed reactor: II. Longevity of the biocatalyst

Abstract: The longevity of the enzyme system for the production of the antibiotic patulin by immobilized Penicillium urticae cells was studied in a three phase fluidized bed reactor. Calculation of the global rate of patulin production indicated that, if the cells were not allowed to grow, the production of patulin gradually declined and stopped at 320 h. Intermittent pulse additions of nutrients stimulated the slow growth of the cells and resulted in an extended production time of 525 h. This long term production was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…The major reason for this reduced productivity would seem to be that the overall cellular activity was adversely affected by longterm exposure to carbon limitation conditions. Similar results have been reported in previous studies (6,8,19,23,37). Table 1 summarizes the results of the continuous operation and compares them with those from a conventional suspended-batch culture.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The major reason for this reduced productivity would seem to be that the overall cellular activity was adversely affected by longterm exposure to carbon limitation conditions. Similar results have been reported in previous studies (6,8,19,23,37). Table 1 summarizes the results of the continuous operation and compares them with those from a conventional suspended-batch culture.…”
Section: Resultssupporting
confidence: 84%
“…When growth is strictly limited to avoid excessive growth, the productivity is often severely reduced. Moreover, the polymer beads are destroyed by the shear force resulting from agitation or mycelial growth inside the beads (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available reports on antibiotic production with immobilized cells are confined to shake flask studies, and only a few reports are available on the bioreactor studies. Successful operation of a 3-phase fluidized bed reactor using immobilized Penicillium urticae with 35% higher patulin antibiotic production was reported by Berk et al 1 Sarra et al 2 showed continuous production of antibiotic by Streptomyces livigans in a 3-phase fluidized bed reactor with self-aggregated immobilized cells for longer periods of time. In addition, reports are also available on nutritional influence on effective continuous production of bacitracin, patulin, and penicillin by various organisms.…”
Section: Introductionmentioning
confidence: 87%
“…Scott, 1983;Deverell and Clark, 1985;Brohan and McLoughin, 1984), -immobilized microorganisms (e.g. Kalogerakis et al, 1986;Fukuda et al, 1984;Scott, 1983;Bailey et al, 1987;Gommers et al, 1986;Webb et al, 1986a;1986b, Berk et al, 1984Behie et al, 1987;Oh et al, 1987), -immobilized animal cells (e.g. Dean et al, 1987;Maffia 1988, Ijima et al, 1988, -primary metabolite production (e.g.…”
mentioning
confidence: 99%
“…Scott, 1983), -production of secondary metabolites (e.g. Kalogerakis et al, 1986;Berk et al, 1984;Behie et al, 1987, Oh et al, 1987, -enzyme production (e.g. Fukuda et al, 1984;Webb et al, 1986).…”
mentioning
confidence: 99%